Quantificação de nitrito em produtos cárneos embutidos - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The objective of this work was to determine the concentration of total nitrite in meat products commercialized in the city of Itaqui-RS. Thirty-six samples of sausages (sausage, mortadella and mixed cooked smoked sausage) were collected from different brands and batches, whichwere analyzed in triplicate for total nitrite content through molecular electronic spectroscopy, according to official methodology. The data from this study allowed us to verify that there was a significant difference between the batches of all brands evaluated. In addition, 25.0% of the brands had nitrite levels above the limit established by Brazilian legislation (150 mg / kg). The B mark of the sausage meat product had a value (227.69 mg / kg of total nitrite) 1.52 times (51.8%) higher than the maximum tolerance permitted by law. The consumption of only 20g of this product in a day, may already develop some toxic symptom to health, as it will exceed the Recommended Daily Intake. Therefore, this research showed the negligence of the industries regarding the standardization of their cured products and the lack of inspection of the competent organs, as a consequence of the excessive quantities of nitrite used in the formulation of foods.
Keywords: Aditivos; Espectrofotometria; Intoxicação; Legislação; Additives; Spectrophotometry; Intoxication; Legislation; CNPQ::CIENCIAS AGRARIAS